Stereopsis before and after surgical treatment for constant versus intermittent exotropia - I. M. Boichuk; Alui Tarak (Journal of Ophthalmology, 2021)
Background: Exophoria may be caused by congenital or acquired anomalies in orbital structure, ocular structure, extraocular muscle attachment and/or extraocular muscle location. Some researchers believe that the presence of stereopsis after treatment for strabismus indicates that a stable treatment outcome has been achieved and binocular vision regained. The state of stereopsis is believed to be an efficacy endpoint in the evaluation of strabismus surgery.